"Pacific ways" of talk: Hui and talanoa - David Robinson; Kayt Robinson (New Zealand Institute of Economic Research (NZIER), 2005)
In this case study we explore the 'Pacific way' of talking about issues of common concern with reference to two customary forms of talk that continue in current use in Fiji and Aotearoa (the Maori name for New Zealand). Taken together they provide an insight into an approach to collective talk, especially the importance of ceremony, which has commonalities with that used in other customary societies. [...] A key purpose of this research was to identify the key components of customary talanoa and hui and to explore what factors need to be present in order for the process to be of use in contemporary society and the degree to which they must all be present in order for an event to be considered to be authentic.
Keywords: 330; Fidschi; Neuseeland; Politische Willensbildung